Perceived risks and vulnerabilities of employing digitalization and digital data in agriculture – Socially robust orientations from a transdisciplinary process - Zscheischler, Jana; Brunsch, Reiner; Rogga, Sebastian; Scholz, Roland W. (Journal of cleaner production, 2022)
The digitalization of agricultural production and the use of digital data are fundamentally transforming processes, products, and services of the agro-food systems. Digitalization improves efficiency and facilitates sophisticated farm management, thus increasing productivity, efficacy, and profitability. At the same time, it promises many opportunities for a more sustainable and, especially, more ecological and cleaner agricultural production. However, with it comes the potential for a number of unintended side effects and risks that may increase the vulnerability of agricultural production and have, thus far, received scant scientific and societal attention. This article presents the results of a two-year transdisciplinary process that aimed to identify unintended side-effects (short “unseens”) and perceived risks of digitalization in German agriculture. Results base on a triangulation of knowledge integration from the transdisciplinary group process involving twelve representatives from science and practice and an ethnographic qualitative meta-analysis. The findings have shown that, despite digitalization's numerous promises for a more ecological and resource efficient agricultural production, a broad range of risks was perceived by some key stakeholders involved. These risks were anticipated to be caused by unintended negative and uncertain side effects on agro-ecological and social systems. Data rights, the restructuring of the value chain with new market concentrations, power structures and dependencies, changing knowledge requirements for farmers (lacking “digital literacy”), and information asymmetries that may cause potentially negative effects on food security were identified as causal factors. Based on these results, we co-developed socially robust orientations (SoROs) for coping with resulting risks and vulnerabilities. We argue that these SoROs provide perspectives on how anticipated knowledge can be turned into responsible action within the RRI (responsible research and innovation) framework. Finally, with regard to the preventive and anticipatory paradigm of “cleaner production”, our transdisciplinary methodology shows a way to adaptively govern the highly complex socio-technological transitions of digitalization in agriculture in the sense of a sustainability-oriented transformation. •Digitalization comes with many promises, but risks remained unseen so far.•Results from this transdisciplinary process show a broad range of perceived risks.•However, actors' perceptions vary greatly and depend on their values and interests.•This poses challenges for shaping the digitalization in a socially responsible way.•We show how co-developed, socially robust orientations point a way forward.